Weather and climate of Orissa - SUBRAMANIAM, A. R.; DEVI, K. UMA (MAUSAM, 1983)
The need for understanding of weather and climate, particularly in a backward region like the State or Orissa cannot be over emphasised. Various climatic aspects such as temperature, continentality, winds, humidity, rainfall, floods and droughts, climatic types and water balance of selected station have been presented. The paper analysed data collected from India Met. Dep. since 1920 to 1978 as per the availability of records. Increase of network of stations is suggested.